33 upvotes00 downvotes

650 views7 pagesFeb 16, 2016

© © All Rights Reserved

PDF, TXT or read online from Scribd

© All Rights Reserved

650 views

33 upvotes00 downvotes

© All Rights Reserved

You are on page 1of 7

1.

2 + 2 + 2 2 + 2 3 + (11) = 0

points (3, 4), (3, 2), and (1, 4)

+ + =

2.

Show that the points (1, 1), (-6, 0), (-2, 2) and (-2, 8) are concyclic.

+ + + + =

Sol: Let A (1, 1), B (-6, 0), C (-2, 2) and D (-2, -8)

(3)2 + (4)2 + 2 3 + 2 4 + = 0

+ + + + =

9 + 16 + 6 + 8 + = 0

+ + + = . ()

(1)2 + (1)2 + 2 1 + 2 1 + = 0

1 + 1 + 2 + 2 + = 0

(3)2 + (2)2 + 2 3 + 2 2 + = 0

+ + + = . ()

9 + 4 + 6 + 4 + = 0

+ + + =

(6)2 + (0)2 + 2 6 + 2 0 + = 0

36 + 0 12 + 0 + = 0

(1)2 + (4)2 + 2 1 + 2 4 + = 0

+ + + =

1 + 16 + 8 + 0 + = 0

+ + + = . . ()

(2)2 + (2)2 + 2 2 + 2 4 + = 0

4 + 4 4 + 4 + = 0

6 + 8 + + 25 = 0

+ + + = . . ()

6 + 4 + + 13 = 0

0 + 4 + 12 = 0 { 4}

2 + 2 + + 2 = 0

+ + = . ()

12 + 0 + + 36 = 0

14 + 2 34 = 0

6 + 4 + + 13 = 0

+ = . ()

2 + 8 + + 17 = 0

4 4 4 = 0 { 4}

12 + 0 + + 36 = 0

= . ()

4 + 4 + + 8 = 0

8 4 + 28 = 0

(5)

{ 2}

{ 4}

+ = . ()

-1

-1

Solving eqn

(g, f)=

1+3 3+0

01

01

1 1

= (2, 3)

(4 ) &

(5)

-17

-7

(g, f)=

7+17 34+49

72

72

10 15

5

= (2, 3)

6(2) + 8(3) + + 25 = 0

12 24 + 25 + = 0 = 11

2(2) + 2(3) + + 2 = 0

, = 0

4 + 6 + 2 + = 0 = 12

, = 0

2 + 2 + 2 2 + 2 3 + (12) = 0

0 + 2 + + 1 = 0

8 + 10 + + 41 = 0

+ + + =

Since D (-2, -8) also lies on S=0

8 8 40 = 0

{ 8}

+ + = . ()

=4 + 64 8 48 12

= 68 68 = 0

.

3.

Solving eqn

-2

If (2, 0), (0, 1), (4, 5) and (0, c) are concyclic, and

then find the value of c.

103 320

+ + + + =

4(

(2)2 + (0)2 + 2 2 + 2 0 + = 0

4 + 0 + 4 + 0 + = 0

4+2

13

6

26

3

17

(g, f)=

13

4+2

)++4= 0

4=

2612

14

3

, = 0

2 + 2 + 2

+ + + = . ()

13

2 + 2

13

+2

17

17

14

+( )=0

6

14

3

=0

(0)2 + (1)2 + 2 0 + 2 1 + = 0

0 + 1 + 0 + 2 + = 0

(0)2 + (c)2

+ + + =

17

3

13

3

14

3

(0)

17

3

=0

3c 2 17c + 14 = 0

C (4, 5) lies on S=0,

(4)2 + (5)2 + 2 4 + 2 5 + = 0

16 + 25 + 8 + 10 + = 0

+ + + = . . ()

3c 2 3c 14c + 14 = 0

3c[c 1] 14[c 1] = 0

1 3 14 = 0

1 = 0 3 14 = 0

= 1 =

4 + 0 + + 4 = 0

0 + 2 + + 1 = 0

4 2 + 3 = 0

+ = . ()

14

3

() +

14

3

=0

4.

X-axis and passing through

(-2, 3), (4, 5)

5.

points (4, 1), (6, 5)and whose centre lies on the

line + = .

+ + + + =

+ + + + =

(2)2 + (3)2 + 2 2 + 2 3 + = 0

(4)2 + (1)2 + 2 4 + 2 1 + = 0

4 + 9 4 + 6 + = 0

16 + 1 + 8 + 2 + = 0

+ + + = . ()

+ + + = . ()

(4)2 + (5)2 + 2 4 + 2 5 + = 0

(6)2 + (5)2 + 2 6 + 2 5 + = 0

16 + 25 + 8 + 10 + = 0

36 + 25 + 12 + 10 + = 0

+ + + =

+ + + =

4 + 6 + + 13 = 0

8 + 2 + + 17 = 0

8 + 10 + + 41 = 0

12 + 10 + + 61 = 0

12 4 28 = 0 { 4}

4 8 44 = 0 { 4}

+ + = . ()

+ + = . ()

, 4 + 3 24 = 0

(, )

4 + 3 24 = 0

. . , =

+ + = ()

= 0 (3)

3 + 0 + 7 = 0

11

3 = 7

24

(g, f)=

3

+ 13 + = 0 =

2839

3

67

7

3

15

5

20

5

8(3) + 2(4) + + 17 = 0

24 8 + 17 + = 0 = 15

67

+2 0 +( )=0

( + ) =

38

, = 0

2 + 2 + 2

(1)

4( ) + 6(0) + + 13 = 0

28

38

= (3, 4)

4833 4424

, = 0

2 + 2 + 2 3 + 2 4 + (15) = 0

+ + = .

7.

Show that the circles + + =

, + + + = touch each other.

Find the point of contact and eqn of tangent at

point of contact.

6.

x2

+ y2

+ = , + + +

+ = touch each other. Find the point of

Sol: eqn s of the given circles

S x 2 + y 2 4x 6y 12 = 0 . . (1)

6x 2y + 1 = 0 . . (1)

S x 2 + y 2 + 6x + 18y + 26 = 0 . . (2)

S x 2 + y 2 + 2x 8y + 13 = 0 . . (2)

, : C1 3, 1 ,

, : C1 2, 3 ,

=

+

=

1 =

32

+ 12

2 =

12

42

1=

1 = 22 + 32 + 12 = 4 + 9 + 12 = 5

=3

2 = 32 + 92 26 = 9 + 81 26 = 64 = 8

13 = 17 13 = 4 = 2

(2 1 )2 + (2 1 )2

1 2 =

=

32

1 3

+ 41

1 2 =

=

1 2 Internally in the

ratio 1 : 2 = 3: 2 = :

2 + 1 2 +1

3+6 12+2

x2

3+2

.

1 2 Internally in the

ratio 1 : 2 = 5: 8 = :

3+2

P=

2 + 1 2 +1

5 3 +8(2) 5 9 +8(3)

5+8

5+8

3 14

5

y2

6x 2y + 1 = 0

y2

+ 2x 8y + 13 = 0

+ 93

3 1 +2(3) 3 4 +2(1)

= 0

x2

1 2 = 1 + 2

3 2

1 2 = 1 + 2

P=

(2 1 )2 + (2 1 )2

(4)2 + (3)2 = 25 =5

C2 3, 9

C2 1, 4

-8x+6y -12=0 { 2}

4 3 + 6 = 0.

15+16 45+24

13

1

13

21

13

= 0

x 2 + y 2 4x 6y 12 = 0

x 2 + y 2 + 6x + 18y + 26 = 0

-10x-246y -38=0 { 2}

5 + 12 + 19 = 0.

8.

4 18 = 3 + 3

+ + = , + +

+ = .

3 + 4 21 = 0.

3 + 4 21 = 0 1 = 0.

S x 2 + y 2 4x 10y + 28 = 0 . . (1)

9.

x2

y2

+ + = , +

+ + = .

+ 4x 6y + 4 = 0 . . (2)

, : C1 2, 5 ,

C2 2, 3

1 = 22 + 52 28 = 4 + 25 28 = 1

, : C1 11, 2 , C2 11, 2

2 = 22 + 32 4 = 4 + 9 4 = 9 = 3

2 2

+ 35

= 225 = 15

= 25 = 5

. .

1 2

Internally in the ratio 1 : 2 = 1: 3 = :

2 + 1 2 +1

2+6 3+15

2 =

1 2 > 1 + 2

P=

1 =

(4)2 + (2)2 = 16 + 4 = 20

4 18

4

(2 1 )2 + (2 1 )2

1 2 =

=

1 2 +3(2) 1 3 +3(5)

1+3

(2 1 )2 + (2 1 )2

1 2 =

1+3

11 + 11

= (1, )

1 2 > 1 + 2

. .

9

2

= 1

2 9

2

1 +1 +

2 1

4 2 +4

=1

And

1

0

9

2

44 8

2

31

31

= (22, 4)

2 1 = 2

=

1 1=0

=

3

4

1 +1 +

2 + 2

11 1 2 22 4

( )2 +(1)2

3 11 1(11) 3 2 1(2)

22 4 = 0 (1)

=

S.O.B.S

3 = 4 =

+ 4 = 22 + 4 = 22

=1

42 + 1 4 = 42 + 4

33+11 62

(2 1)2 = 42 + 4

2 + 2

2 (2)2(5)2 +9

2 + 1 2 +1

P=

1 1 = 1

(2 )2 +(2)2

1 2

Internally in the ratio 1 : 2 = 15: 3 = 3: 1:

= 1

2 2 2 + 9 = 0 (1)

=

+ 2 2

11 2

2 +1

=5

=5

S.O.B.S

1212 + 4 + 44 = 252 + 25

962 + 44 21 = 0

through a point p to the circle x2+y2=r2, then find

locus of p when cot + =k.

962 + 72 28 21 = 0

24 4 + 3 7(4 + 3) = 0

24 7 4 + 3 = 0

24 7 = 0 4 + 3 = 0

7

24

, =

3

4

+4 =

7

24

22 24 + 96 = 7 156

7 24 250 = 0.

And

+4 =

3

4

22 4 + 16 = 3 + 66

3 + 24 50 = 0.

(1)

: Let P(x1, y1) be the any point on the locus

Equation of tangent through p with slope m is

Y= 1 + 2

This passes through P(x1, y1)

1 =1 1 + 2

1 -1 = 1 + 2

S.O.B

(1 1 )2 = ( 1 + 2 )2

1 2 + 2 1 2 21 1 = 2 (1 + 2 )

1 2 + 2 1 2 21 1 = 2 + 2 2 )

2 1 2 2 21 1 + 1 2 2 = 0

Where m1, m2 be the slopes of the tangents

which make angles 1 , 2

m1=tan1 , m2=tan2

Given cot1 + cot 2 =k.

3 + 24 50 = 0 7 24 250 = 0.

1 2

1

1

1 2

2 1

1 2

1 + 2 = 1 2

2x-3y+1=0 at (1, 1) and having radius .

Sol: given two circles touch the line

2 3 + 1 = 0 (1)

(1, 1)

= 13

The centres

1 , 2

1 1 , 1 = (1, 1)

2

3

3

Slope of (1) = - ( ) =

Slope of line 1 2 =

3

= =

=

3

13

2

13

The centres 1 , 2

= 1 , = 1

= 1 13

2

13

, 1 13

3

13

= {1(2), 1 3}

= (1-2, 1+3) and (1+2, 1-3)

= (-1, 4) and (3, -2)

Eqn of the circle with 1 1, 4

= 13

2

( + 1)2 +( 4)2 = 13

x 2 + y 2 + 2x 8y + 4 = 0

Eqn of the circle with 2 3, 2

= 13

( 3)2 + ( + 2)2 = 13

x 2 + y 2 6x + 4y = 0.

2 1 1

1 2 2

1 2 2

1 2 2

(1 2 2 )

21 1 =

The equation of locus of P(x1, y1) is

2 = ( 2 2 )

x2+y2=r2 w.r.to the circle (x + a) 2+y2=2a2 lie on

y2+4ax=0.

Sol: Let P(x1, y1) be the pole of tangents of the

circle x2+y2=r2 w. r. to the circle S(x + a)

2+y2=2a2

x 2+y2 +2ax-a2=0

Now the polar of p w.r.t to S=0 is S1=0

xx1+yy1+a(x+x1) - a2=0

x(x1+a) +yy1+ (ax1- a2) =0.. (1)

1 + + = 0,

= 1 + , = 1 , = 1 a2

+ + = 0

2 + 2 = 2 2 = 2 ( 2 + 2 )

(1 2 )2 = 2 {(1 + )2 + 1 2 }

2

{ 1 2 = 2 {(1 + )2 + 1 2 }

1 2 + (1 + )2 (1 )2 = 0 1 2 +

41 = 0

the equation of locus of P(x1, y1) is y2+4ax=0

13. If the chord of contact of a point P with respect to

that AOB =900 then show that P lies on the circle

x2+y2=2a2.

Sol: Given circle x2+y2=a2... (1)

Let p(x1, y1) be a point and let the chord of

contact of it cut the circle in A and B such that

AOB=900. The equation of the chord of contact

of p(x1, y1) with respect to (1) sis xx1+yy1a2=0.. (2)

The equation to the pair of lines OA and OB is

given by x2+y2-a2

1 + 1 2

2

=0

Or 2 x 2 + y 2 1 + 1 2 = 0

2 2 1 2 21 1 + 2 2 1 2 = 0

(3)

Since AOB=900, we have the coefficient of

2 3 + 2 3 = 0

2 1 2 + 2 1 2 = 0

1 2 + 1 2 = 22

Hence the point p(x1, y1) lies on the circle

x2+y2=2a2.

tangents drawn from an external point p ( , )

to the circle S=0 is = .

Sol: given that p (x1 , y1 ) is an external point on

S=0 let AB be the chord of contact of P to the

circle S=0 and its equation is 1 = 0

Let Q (x2 , y2 ) be any point on the locus

i.e. , be a point on the pair of tangents

the ratio that the line AB divides PQ can be

determined in 2ways :

(1) PB:QB is equal to 11 : 22 .(1)

(2) The line

1 =

0

11

12

(2)

From (1), (2) we get

11

22

11

11

22

11

12

S.O.B

12 2

11 22 = 12 2

Hence the equation of the locus of

Q (x2 , y2 ) is S1 2 = SS11 .

{ (x2 , y2 ) replaced by (x, y)}

## Much more than documents.

Discover everything Scribd has to offer, including books and audiobooks from major publishers.

Cancel anytime.